On the equivalence of Fechner’s and Stevens’ laws - Romanchak, Vasily M. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
On the basis of the method of subjective measurement, the equivalence of Fechner’s and Stevens’ laws is proved. We consider the classical version of the method of subjective measurement, which axiomatically determined the sequence of objects, the value of which varies uniformly. The number of an element in this sequence is called a rating. It is believed that as a result of a subjective measurement, only a rating can be found. There are two main ways to compare values – absolute and relative. By defining a rating, you can find values using a comparison method. It is shown that the difference between the both laws is a consequence of different methods of comparison, therefore, when replacing the value with the rating, these laws, coincide.
Keywords: expert assessments; rating; Fechner's law; Stevens ' law; utility function; decision making